Sorry to be rude so how do I work out the answer, that example didn't make sense to me?
\(\displaystyle a = b \iff log_c(a) = log_c(b)\ for\ any\ real\ c > 0\ and\ c\ne 1.\)
In words: if two numbers are equal to each other, then their logs (to the same base) are equal; and if two logs to the same base are equal to each other, then their arguments are equal.
You with me?
So
\(\displaystyle 3^x = 10 \implies\)
\(\displaystyle log_c\left(3^x\right) = log_c(10), where\ c > 1.\) Just applying the general rule explained above.
And \(\displaystyle log_c\left(3^x\right) = x * log_c(3).\) One of the basic laws of logarithms, right?
So \(\displaystyle x * log_c(3) = log_c(10).\) Basic rule of algebra: two numbers equal to a third number are equal to each other.
And \(\displaystyle log_c(3) > 0 \implies log_c(3) \ne 0.\) So I can divide both sides of the equation by \(\displaystyle log_c(3).\)
\(\displaystyle x = \dfrac{log_c(10)}{log_c(3)}.\)
Now let's check our answer.
\(\displaystyle y = 3^x\ and\ x = \{log_c(10) \div log_c(3)\} \implies log_c(y) = log_c\left(3^{\{log_c(10) \div log_c(3)\}}\right) = \dfrac{log_c(10)}{log_c(3)} * log_c(3) = log_c(10).\)
\(\displaystyle log_c(y) = log_c(10) \implies y = 10 \implies 3^x = 10.\) It checks.